Auditing ABC University's New Student Registration System Maturity Level Through COBIT 2019 - Indana, Luthfi; Nugroho, Ferdyanto Adhi (Jurnal Sains, Nalar, dan Aplikasi Teknologi Informasi, 2026)
The New Student Admissions Information System (PMB) at ABC University still faces several challenges, such as slow document verification, data inconsistencies, and a monolithic structure integrated with other systems (e.g., SIAKAD), which negatively impacts its performance. This study evaluates the performance of this web-based PMB system using the COBIT 2019 framework. A quantitative approach was employed, with data collected through interviews, observations, questionnaires, and document analysis. The study focuses on the DSS (Deliver, Service, Support) domain of COBIT 2019 to assess the system's maturity level. The analysis reveals that the PMB system's maturity level is 3.78 (Level 4), indicating that processes are well-established but require further optimization to reach Level 5 (Optimizing). To achieve this, PUSIM (Center for Information Technology and Multimedia) must develop and periodically review planning documents to ensure optimal performance of the information system services in line with institutional targets.